EFFECT OF ONLINE COACHING-BASED WORKOUT FOR ENHANCING THE MUSCLE ENDURANCE AND BODY COMPOSITION FOR THE FEMALE MEMBERS OF IMMUNITY FIT CLUB - Kamilah, Hana Sari; Prastyawan, Rifky Riyandi; Prasetyo, Yudik; Delano, Enggista Hendriko (MEDIKORA, 2025)
This research aims to: (1) assess the effect of online coaching-based workouts on enhancing muscle endurance of female members of Immunity Fit Club; (2) evaluate the effect of online coaching-based workouts on regulating body composition of female members of Immunity Fit Club; and (3) analyze the efficacy of online coaching-based workout training programs in enhancing muscle endurance and managing body composition of female members of Immunity Fit Club. This research employed a quantitative method with a quasi-experimental design, focusing on a group of 50 female members from Immunity Fit Club online coaching class. The research sample comprised 22 respondents selected by purposive sampling. This research employed a data collection technique involving an initial assessment by anthropometric measurements to ascertain body composition prior to the training program, followed by subsequent measurements at the program's conclusion. The data analysis method employed the normality test and t-test. The research findings indicate favorable alterations in the body composition of female members of Immunity Fit Club following 18 online coaching sessions utilizing the circuit training method. This fitness training program effectively attain the specified objectives, as shown by alterations in body circumference and weight. T-test examination of muscle endurance reveal a substantial enhancement (p < 0.05) across all evaluated parameters: arm muscles (Push Up, t = -14.289), abdominal muscles (Sit Up, t = -13.420), core muscles (Plank, t = -20.695), and leg muscles (Wall Squat, t = -18.450).